Arcane epipelagic fishes of the subtropical North Pacific and factors associated with their distribution. (January 2017) - McKinnell, Skip; Seki, Michael P.
Highlights: New study of zoogeography of epipelagic fish species in the N. Pacific subtropics. Species composition in driftnet catches was predictable between years. Species distribution was related to meridional and zonal ocean gradients. Zonal variability in species numbers with a trend from west to east. Abstract: In 1992, a moratorium was declared by the United Nations General Assembly to end the practice of large-scale pelagic driftnet fishing. During two years leading up to the moratorium, three scientific research and fishery observer programs involving Canada, Japan, Korea, China-Taipei and the United States had collected significant amounts of information about the distribution and abundance of the epipelagic fauna in the subtropical North Pacific Ocean. The pan-regional distributions of the fishes in 1990 and 1991, most of which were taken as bycatch in 9910 fishing operations (357, 150 km of driftnet) are described. More species were observed per fishing operation in 1991 than in 1990. Principal coordinate analysis of the incidence of the commonly caught fish species was used to show that, except for an anomaly in the region of the Shatsky Rise (165°E), the composition of the catch changed from the coast of Japan across more than 6000 km to the eastern boundary of the fishery (145°W). The analysis suggested that the fish species composition changed rather little with increasing latitude within the southern part of the domain (25–35°N), before changing more rapidly north of the Kuroshio Extension region to a more subarctic, transition zone fauna.